2014
DOI: 10.1021/am503560d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen, Moisture and Illumination on the Stability and Reliability of Dinaphtho[2,3-b:2′,3′-f]thieno[3,2-b]thiophene (DNTT) OTFTs during Operation and Storage

Abstract: We report a systemic study of the stability of organic thin film transistors (OTFTs) both in storage and under operation. Apart from a thin polystyrene buffer layer spin-coated onto the gate dielectric, the constituent parts of the OTFTs were all prepared by vacuum evaporation. The OTFTs are based on the semiconducting small molecule dinaphtho[2,3-b:2',3'-f]thieno[3,2-b]thiophene (DNTT) deposited onto the surface of a polystyrene-buffered in situ polymerized diacrylate gate insulator. Over a period of 9 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Since registration is difficult for the small nozzle, a slight off-set of 0.5 mm was applied to each substrate in the drum width direction, in order to ensure that at least one row of transistors was well registered with the jet. as hole traps reported previously [25].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Since registration is difficult for the small nozzle, a slight off-set of 0.5 mm was applied to each substrate in the drum width direction, in order to ensure that at least one row of transistors was well registered with the jet. as hole traps reported previously [25].…”
Section: Resultssupporting
confidence: 73%
“…The lauryl acrylate buffered sample showed slightly more negative turn-on and threshold voltages than for the PS buffer, likely due to its slightly higher surface polarity and hence affinity for water. It is known that absorbed atmospheric moisture can be a source of hole traps which is reflected in transfer curves as a more negative turn-on voltage and eventually lower mobility [25]. The un-buffered transistor in this work showed carrier mobility of ~0.05 cm 2 /Vs, on/off ratio of 10 4 and turn-on voltage close to 0 V. The low mobility was likely due to the undesirable surface energy which is prone to yielding poor crystallinity at the very near surface in deposited films of small molecule semiconductors as discussed in our recent paper [23].…”
Section: Resultsmentioning
confidence: 99%
“…No drift of µ or V T were observed after 20 000 cycles of the transfer characteristics or after 24 h under constant direct‐current bias stress. OFETs were also air stable >200 d. Thienoacenes, such as DNTT 9 ( R = H or C 10 H 21 ) show excellent device stability over periods of several months . Thermal stability of OFETs was also demonstrated for DNTT 9 ( R = phenyl) .…”
Section: Charge Transportmentioning
confidence: 93%
“…However, this is not the case for DNTT-based TFTs. A recent study showed that moisture led to negative shifts of threshold and turn-on voltages, and an increase in off-current [16]. The measured mobility appeared to be unaffected.…”
Section: Introductionmentioning
confidence: 97%